Analysis on the centralized and decentralized trading in a three- bus system using MATLAB Graphic User Interface (GUI) / Muhd.Dzulfikrie Hipni - Hipni, Muhd.Dzulfikrie (2017)
This project is about the analysis on Centralized and Decentralized trading in a three bus system by using MATLAB Graphic User Interface (G.U.I). The main objective of this project is to design the educational software that helps power system students in understanding the issues of the Centralized and Decentralized trading on Transmission Network & Electricity Markets. There are various types of customized toolboxes developed that can be used to design the program specifically for education purpose and research finding such as such as Power System Analysis Package (P SAP AC) and Power System Simulator (Simpow), but most of them are complex programs that difficult to be used and having least capacity of visualization compared to the GUI in MATLAB. Besides that, the GUI software is more suitable to visualize the effect changes in the system parameters by having an attractive and simple look interface for Centralized and Decentralized trading to make it easy to be used by the students. The software consists of two main parts, Centralized and Decentralized trading. For the Centralized trading, the users will able to define the optimum economic dispatch cost, power flow of each branch, power generator unit, overloading problem and new economic dispatch obtained after the deal with the overload problem. Meanwhile, the Decentralized trading analysis shows the recommended magnitude of the power flow in each branch based on the inserted power load demand. Thus, this software is able to increase student's understanding regarding on the concept, operation and theoretical calculation of each type of trading in the three-bus system. There is one survey that has been conducted to gauge on the efficiency, the accuracy of the tool to producing the output and the rate of satisfaction of the respondents when using the C&D software was conducted among the Electrical Engineering student are studied at Universiti Teknologi MARA (UiTM) Shah Alam.